2011
DOI: 10.1016/j.jmoldx.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Dropout Can Cause False-Positive Results for Prader-Willi and Angelman Syndrome Testing

Abstract: The diagnosis of many genetic disorders relies on a combination of clinical suspicion and confirmatory genetic testing. Our laboratory uses a standard methylation-sensitive PCR (MSP) to target the differentially methylated SNRPN gene to test for Prader-Willi syndrome (PWS) and Angelman syndrome. One patient, a 27-month-old female, who lacked the classical clinical features of PWS, but had a molecular diagnosis of PWS by MSP by another laboratory, had repeat testing in our laboratory. Testing by MSP in our labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…One case showed two large AOH regions of 40.6 Mb (15q11.1-15q22.2) and 12.4 Mb (15q26.1-15q26.3) interrupted by a region of heterozygosity (Supplementary Figure 2 ), a condition which was suspected to be from uniparental disomy (UPD). Methylation-specific polymerase chain reaction (MS-PCR) analysis of SNRPN gene was then performed using primers as previously described 36 , 37 , and the results confirmed that this patient had maternal uniparental isodisomy of the 15q11.2 region resulting in Prader-Willi syndrome (Supplementary Figure 3 ). Additionally, multiple large AOH regions (average 158.02 Mb) were also detected in another patient, encompassing 5.84% of the genome (data not shown), suggesting a consanguineous marriage between first cousin parents (coefficient of inbreeding (F) 1/16).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…One case showed two large AOH regions of 40.6 Mb (15q11.1-15q22.2) and 12.4 Mb (15q26.1-15q26.3) interrupted by a region of heterozygosity (Supplementary Figure 2 ), a condition which was suspected to be from uniparental disomy (UPD). Methylation-specific polymerase chain reaction (MS-PCR) analysis of SNRPN gene was then performed using primers as previously described 36 , 37 , and the results confirmed that this patient had maternal uniparental isodisomy of the 15q11.2 region resulting in Prader-Willi syndrome (Supplementary Figure 3 ). Additionally, multiple large AOH regions (average 158.02 Mb) were also detected in another patient, encompassing 5.84% of the genome (data not shown), suggesting a consanguineous marriage between first cousin parents (coefficient of inbreeding (F) 1/16).…”
Section: Resultssupporting
confidence: 53%
“… 37 and alternative primer sets designed by Hussain Askree et al . 36 . Untreated DNA was used as a control to ensure complete sodium bisulfate conversion of DNA, and amplified using primer set as previously described 36 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inaccuracy of MSP outcome might be for various reasons, such as an incomplete bisulfide conversion, which might result in an overestimation of DNA methylation (47). Another possible source of discrepancies may be allelic dropout or semiallelic methylation (48). Therefore, MSP does not seem to be reliable enough for methylation studies and a subsequent verification of its results by supplementary techniques is desirable (49).…”
Section: Discussionmentioning
confidence: 99%
“…The methylation-specific and non-methylation primers are as follows ( Askree et al, 2011 ): MF 5′-TAAATAAGTACGTTTGCGCGGTC-3′ and MR 5′-AACCTTACCCGCTCCATCGCG-3′ were used to generate the 174 bp methylation product. Primers, PF 5′-GTAGGTTGGTGTGTATGTTTAGGT-3′ and PR 5′-ACATCAAACATCTCCAACAACCA-3′ were used to amplify 100 bp of the non-methylated allele.…”
Section: Molecular Diagnosis Of Prader–willi Syndromementioning
confidence: 99%